THE IMPACT OF CHRONIC CANNABINOID USE AND DEPENDENCE ON OPIOID ANALGESIC TREATMENT – A SYSTEMATIC REVIEW AND PREDICTIVE ANALYSIS - Tomasz Poczwardowski; Adrianna Kaczmarek; Franciszek Szweda; Kinga Augustyniak; Marcin Chwalczuk; Jakub Tomasz Latos; Olivia Grygorcewicz; Marta Koneczna; Katarzyna Anna Kowalska; Karolina Alicja Krystyniak (International Journal of Innovative Technologies in Social Science, 2026)
In recent years, there has been growing interest in cannabinoids as potential analgesics and alternatives to opioids. Cannabinoids, through modulation of the endocannabinoid system, affect nerve transmission, neuroplasticity, and inflammatory processes, and their action on CB1 and CB2 receptors is similar to the mechanisms of the opioid system, in particular μ, δ, and κ receptors. The aim of this study was to compare the mechanisms of action of cannabinoids and opioids, review studies on their combined use, and assess the impact of chronic cannabinoid use and dependence on the effectiveness of opioid-based pain treatment. Analysis of the available data showed that moderate use of cannabinoids, especially preparations with a balanced THC and CBD content, can lead to an "opioid-sparing" effect, allowing opioid doses to be reduced without losing the analgesic effect. However, chronic use of cannabinoids, especially those with high THC content, is associated with the development of tolerance, mood disorders, desensitization of CB1 receptors, and disturbances in the co-regulation of μ receptors, which may lead to compensatory escalation of opioid treatment and the development of cross-addiction. In addition, partial clinical benefits have been observed in patients with neuropathic pain from the combination of cannabinoid and opioid therapy, while no clear analgesic effects have been observed in acute pain. The proposed predictive model integrates molecular, clinical, and psychological aspects, indicating that the effectiveness of analgesic therapy depends on the duration of exposure to cannabinoids, the type of pain, and the individual predisposition of the patient. The authors point to the need for further research involving patients who are chronic users of cannabinoids or addicted to them and who are scheduled to be treated with opioids. The results of such analyses could form the basis for the development of clinical guidelines for integrated pain therapy that minimizes the risk of addiction and treatment failure.